The Implementation of Career Guidance Services in Enhancing Students' Readiness for Admission to Public Universities - Noor Hijriati; Muhammad Zuhaery; Ika Maryani (Journal of Science and Education (JSE), 2026)
Students' readiness for admission to State Universities (PTN) requires systematic and sustained career guidance services. This study explores the implementation of career guidance services at SMAIT Istiqamah Balikpapan in supporting students' readiness for higher education. A descriptive qualitative approach was employed involving the principal, vice principals, guidance and counseling teachers, homeroom teachers, and teachers responsible for university preparation. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that career guidance is implemented continuously from Grade 10 through four integrated services: information and further study exploration, counseling and major selection assistance, academic readiness strengthening, and psychological and administrative support. These services are collaboratively delivered by school leaders, teachers, parents, alumni, and external partners. According to school staff, the integrated implementation of these services supports students in understanding higher education options, selecting appropriate study programs, strengthening academic preparation, and enhancing confidence for university admission. The findings highlight the importance of sustained, collaborative career guidance in facilitating students' readiness for higher education.